1993
DOI: 10.1007/bf00158794
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of antibodies to Chlamydia Psittaci and Coxiella Burnetii through eggs and “crop milk” in pigeons

Abstract: Young semi-domesticated pigeons captured or hatched from eggs gathered in Bratislava during 1989-1991 were examined for complement fixing antibodies to Chlamydia psittaci and agglutinating antibodies to Coxiella burnetii. Antibodies to Ch. psittaci were present in 76% of birds younger than 24 h, in 47.7% between 1 and 10 days of age and in 12% of nestlings over 10 days old. Antibodies to Ch. psittaci were also detected in "crop milk" of 4.1% of 1 to 10 day old birds and in 4.5% of specimens older than 10 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Unlike mammals, both male and female pigeons produce pigeon milk ( Gillespie et al, 2012 ). Pigeon milk contains protein (60%), fat (32–36%), carbohydrate (1–3%), minerals (calcium, potassium, sodium, and phosphorus), and antibodies ( Davies, 1939 ; Kocianova et al, 1993 ). Up to 7 days of age, squabs mainly rely on pigeon milk to obtain nutrients, while between 8 and 14 days of age, the pigeon milk includes a large amount of food initially digested by their parents ( Horseman and Buntin, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mammals, both male and female pigeons produce pigeon milk ( Gillespie et al, 2012 ). Pigeon milk contains protein (60%), fat (32–36%), carbohydrate (1–3%), minerals (calcium, potassium, sodium, and phosphorus), and antibodies ( Davies, 1939 ; Kocianova et al, 1993 ). Up to 7 days of age, squabs mainly rely on pigeon milk to obtain nutrients, while between 8 and 14 days of age, the pigeon milk includes a large amount of food initially digested by their parents ( Horseman and Buntin, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in a 1952 study where pigeon 'milk' was fed to chickens, their rate of growth improved by 38% [6]. Since this study, it has been shown that pigeon 'milk' contains IgA antibodies [7,8], which provides further evidence to suggest that it is more than a nutrient based substance.…”
Section: Introductionmentioning
confidence: 68%
“…However, it is still unclear whether such antibodies cross the gut barrier of the young (Apanius 1998). Postnatal transmission of antibodies is believed to be particularly important in altricial species with similar postnatal feeding to pigeons, as it could limit the transmission of infections through regurgitation of infected materials (Brand 1989; Kocianova, Rehacek & Lisak 1993). Similar mechanisms could have evolved in other bird species through the transmission of antibodies in the saliva (Apanius 1998).…”
Section: Discussionmentioning
confidence: 99%